Effect of intraradicular fiber post on the fracture resistance of endodontically treated and restored anterior teeth: A systematic review and meta-analysis - Jurema, Ana Luiza Barbosa [UNESP]; Filgueiras, Amanda Tauchen [UNESP]; Santos, Kamilla Alves [UNESP]; Bresciani, Eduardo [UNESP]; Caneppele, Taciana Marco Ferraz [UNESP] (Elsevier, 2021)
Statement of problem: A fiber post is indicated when there is a significant loss of tooth structure and additional support for the restoration is needed. However, whether the use of a glass fiber post affects the fracture susceptibility of the restored anterior teeth is unknown. Purpose: The purpose of this systematic review and meta-analysis was to evaluate the fracture resistance of endodontically treated and restored anterior teeth and to answer the research question, “Does the use of a fiber post influence the fracture resistance of endodontically treated and restored anterior teeth compared with alternative restorative treatments?” Material and methods: A search was performed in PubMed, Scopus, Web of Science, LILACS, BBO, Cochrane Library, and Embase databases without date and/or language restrictions (updated in July, 2020). In vitro studies comparing the fracture strength of endodontically treated and restored anterior teeth with and without fiber posts were included. The risk of bias was evaluated by using the previous meta-analyses of in vitro studies. The results were presented as standardized mean difference with a 95% confidence interval. Statistical heterogeneity of treatment effects between studies was assessed using the Cochran Q test and the I2 inconsistency test, and values greater than 50% were considered indicative of substantial heterogeneity. Results: After the removal of duplicates and title and abstract screening, 31 studies remained. Seventeen were considered low risk of bias, 10 were medium risk of bias, and 4 were high risk of bias. Meta-analysis comparing control and experimental groups favored the use of a fiber post in endodontically treated teeth with some types of restoration to improve fracture resistance (standardized mean difference= 0.5 [0.08; 0.92]); a glass fiber post was also favored (standardized mean difference=0.92 [0.43; 1.42]); for veneer preparations and teeth with cervical cavities, a fiber post increases the fracture strength (standardized mean difference= 0.74 [0.01; 1.47]; 1.18 [0.35; 2.02], respectively). Conclusions: The use of glass fiber posts increases the fracture resistance of endodontically treated and restored teeth.